La política científica colombiana desde 1990 (2019)
Since 1990 Colombia and the Latin American countries have had changes in their public policies as one of their purposes orients the economy towards productivity and competitiveness involving science, technology and innovation (CTeI). Development plans are implemented through the National Economic and Social Policy Coun-cil (CONPES), the body in charge of monitoring, control and evaluation. In this sense, the purpose of the article is to analyze the dynamics of Colombian scientific policy in development plans since 1990. The research focus is qualitative-quantitative, as it integrates design, document review, content analysis, analysis of indicators and comparison of figures. Among the main results stand out how the implementation of scientific policy has not been in accordance with the development plans of the first five governments, even so, the results from 2010 onwards describe favorable trends. It concludes with the need to increase the action of state agencies and the articulation with the productive sectors with a view to strengthening the formulation of a coherent and contextualized scientific policy.